Dependence of mechanical characteristics from composition and structure and optimization of mechanical fracture energy of polymer composite material based on high-molecular rubbers (Fracture and Structural Integrity, 2017)
By means of numerical experiment the authors investigate dependence of conventional rupturing stress and mechanical fracture energy at uniaxial tension from fractional composition of dispersed filler, plasticizer volume fraction in polymer binder, effective density of transverse bonds, applied to development of covering for different purposes and with advanced service life in temperature range from 223 to 323 K. They compare mechanical characteristics of polymer composite materials (PCMs) based on high- and low-molecular rubbers. It was shown that rupturing stress of high-molecular rubber-based PCM is of a higher magnitude than the stress of low-molecular rubber-based one at almost invariable rupturing deformation. Numerical simulation by variation of composition parameters and molecular structure enables evaluation of its maximum fracture energy which is 1000 times higher than mechanical fracture energy of similar composites based on low-molecular rubbers.
Keywords: High-molecular rubbers; Deformation; Composites; Mechanical stress; Envelopes of fracture points; Optimization; Plasticizer; Polymer composite; Linking; Glass transition temperature